The Effects of Corruption On Socio-Economic Development in Kenya - Ogembo, Paul Okeyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
Corruption is real in the societies, Kenya not excluded. Corruption has serious ramifications on socio-economic development in the society on the issue of depriving the common citizens towards realizing necessary development initiatives and equity in resource distribution. The purpose of the study was to determine the effects of corruption on socio-economic development in Kenya. Specific objectives were to establish: effects of corruption on infrastructural development and on access to tenders with the governments of Kenya. The study adopted meta-analyses of empirical literature supported by Ferrer (1998) The study established that corruption is entrenched in Kenya. That corruption has led to exaggeration of the costs of infrastructural projects in Kenya and or led to some being stalled. That getting tenders with the government is not easy but depends on connections. The findings have implications on strengthening the government institutions like anti-corruption commission, the office public prosecutor, the Directorate of Criminal Investigation the court system to be strengthened proper investigations be done prosecuting and trial of those found culpable.